Therapeutic Effects of Melatonin in Lead-Induced Toxicity in Rats - G. Alabbassi, Mustafa; A. Hussain, Saad; H. Ali, Shatha (Iraqi Journal of Pharmaceutical Sciences, 2017)
Exposure to lead results in significant accumulation in most of vital organs, and free radical damage has been proposed as a cause of lead-induced tissue damage, where oxidative stress is a likely molecular mechanism. This study was designed to evaluate therapeutic effects of melatonin in lead-induced organ toxicity in rats. The therapeutic effects of melatonin on lead induced toxicity in rats were evaluated using 36 rats, which were allocated into 3 groups and treated as follows: Group I, includes 12 rats injected subcutaneously with 0.2 ml physiological saline for 30 days, followed by treatment with a daily dose of 20mg/kg melatonin, administrated I.P for the successive 30 days; groups II and III, each includes 12 rats , injected with lead acetate 100 mg/kg/day s.c for 30 days, followed by treatment with intraperotoneal injection of physiological saline (0.2 ml) or melatonin 20mg/kg/day for the next 30 days. At the end of treatment period, the rats were sacrificed by an overdose (100mg/kg) of thiopental (twenty-four hour after the last injection). Craniotomy and laparotomy were performed to obtain the brains, livers and kidneys for the assessment of tissue damage. The changes in total body weight, weight of major organs (brain, liver and kidney), oxidative stress parameters, hemoglobin content, liver and renal functions, and histological appearance of the studied organs were evaluated and compared with that of negative and positive controls. Treatment with melatonin reverses the damage induced by lead in many organs and tissues through the reduction of MDA levels in RBCs, brain, liver and kidney; increases GSH levels in all studied organs; in addition to the improvement in the indices of the functions of the organs studied. These findings demonstrated that melatonin is capable of reversing damage of rat tissues caused by successive doses of lead acetate, and animals had restored their organ functions due to treatment with melatonin. Key words: Melatonin, Lead poisoning, Oxidative stress